Willful girls : gender and agency in contemporary Anglo-American and German fiction - Jeremiah, Emily (Women and gender in German studies., 2018)
Explores the process of ""becoming woman"" through an analysis of the depiction of girls and young women in contemporary Anglo-American and German literary texts